2012
DOI: 10.1021/ac301510k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pore Sizes and Relative Porosity in Porous Nanoshell Architectures Using Dextran Retention with Single Monomer Resolution and Proton Permeation

Abstract: Unilamellar phospholipid vesicles prepared using the polymerizable lipid bis-sorbylphosphatidylcholine (bis-SorbPC) yield three-dimensional nanoarchitectures that are highly permeable to small molecules. The resulting porous phospholipid nanoshells (PPNs) are potentially useful for a range of biomedical applications including nanosensors and nanodelivery vehicles for cellular assays and manipulations. The uniformity and size distribution of the pores, key properties for sensor design and utilization, has not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…To enhance the stability of the aptamer sensor in biological fluids, we encapsulated the aptamer within a PPN. PPNs are water-filled nanoshells that have an inherent porosity within the nanoshell membrane [34;38]. Prior work has shown that PPNs retain compounds greater than 3 kDa for an indefinite time frame, yet allow unimpeded access of compounds less than 1.5 kDa, irrespective of charge [34;38].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To enhance the stability of the aptamer sensor in biological fluids, we encapsulated the aptamer within a PPN. PPNs are water-filled nanoshells that have an inherent porosity within the nanoshell membrane [34;38]. Prior work has shown that PPNs retain compounds greater than 3 kDa for an indefinite time frame, yet allow unimpeded access of compounds less than 1.5 kDa, irrespective of charge [34;38].…”
Section: Resultsmentioning
confidence: 99%
“…The experiment was performed at 25 (±1) ° C in a refractive index matching solution. Prior works have shown that PPNs retain material with MW larger than the cutoff for indefinite time frames [34;38]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it seems that nearly the full spectrum of polymerizable groups suited for radical polymerization has been used to make polyzwitterions in the past, including not only styrenes, vinylpyridines, vinylimidazoles or vinylesters [124], but also rather uncommon polymerizable groups such as dienoic acids [123,124,[131][132][133][134][135][136][137][138][139], vinylcyclopropanes [124,134] or isocyanides [69], and cyclopolymerizing species such as diallylammonium [64,87,88,124,134,[140][141][142][143][144][145][146][147][148][149][150][151][152][153] and closely related divinyl monomers [93,94]. Moreover, a number of monomers confined exclusively to (often alternating) radical copolymerization, such as vinylethers [124,134], fumarates and maleates [124,134,[154][155][156], isobutylenes [157] and ...…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%